The ensemble ebook A novel. - Gabel, Aja (2018)
"Pitch-perfect." — People "You won’t be able to quit these characters."  —goop The addictive novel about four young friends navigating the cutthroat world of classical music and their complex relationships with each other, as ambition, passion, and love intertwine over the course of their lives. Jana. Brit. Daniel. Henry. They would never have been friends if they hadn't needed each other. They would never have found each other except for the art which drew them together. They would never have become family without their love for the music, for each other. Brit is the second violinist, a beautiful and quiet orphan; on the viola is Henry, a prodigy who's always had it easy; the cellist is Daniel, the oldest and an angry skeptic who sleeps around; and on first violin is Jana, their flinty, resilient leader. Together, they are the Van Ness Quartet. After the group's youthful, rocky start, they experience devastating failure and wild success, heartbreak and marriage, triumph and loss, betrayal and enduring loyalty. They are always tied to each other - by career, by the intensity of their art, by the secrets they carry, by choosing each other over and over again. Following these four unforgettable characters, Aja Gabel's debut novel gives a riveting look into the high-stakes, cutthroat world of musicians, and of lives made in concert. The story of Brit and Henry and Daniel and Jana, The Ensemble is a heart-skipping portrait of ambition, friendship, and the tenderness of youth.